Analisis Yuridis Sengketa WTO Atas Larangan Impor Produk Pertanian Ukraina oleh Polandia - Indah Ayu D.M; Davina Nisrinaila I.P; Cindi Fadila; Igha Kinayungan; Zukrufi Ashof Almaunah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The Russia–Ukraine armed conflict has disrupted global food supply chains by blocking Black Sea export routes, forcing Ukraine to redirect its agricultural exports through neighboring countries, particularly Poland. The resulting oversupply of Ukrainian agricultural products in the Polish domestic market triggered a unilateral import ban in April 2023, which subsequently gave rise to WTO dispute WT/DS619. Previous studies have predominantly examined this issue from economic and geopolitical perspectives, while limited attention has been devoted to assessing the compatibility of Poland’s import restrictions with the legal framework of the General Agreement on Tariffs and Trade (GATT) 1994, the Agreement on Agriculture, and the Dispute Settlement Understanding (DSU). This study aims to analyze the legality of Poland’s import ban and evaluate the WTO dispute settlement mechanism applicable to the dispute. Using a normative legal research method with statutory and case approaches, this study examines WTO legal instruments, official dispute documents, and relevant academic literature. The findings indicate that although Poland justified the import ban as a temporary measure to protect its domestic agricultural market, the measure potentially constitutes a quantitative restriction prohibited under Article XI:1 GATT 1994, restricts the freedom of transit under Article V:2, raises concerns regarding transparency under Article X:1 GATT 1994, and is potentially inconsistent with Articles 4.2 and 5 of the Agreement on Agriculture, as it imposes non-tariff restrictions outside the WTO safeguard framework. Furthermore, the study finds that Ukraine’s decision to remain at the consultation stage under the DSU reflects not only procedural considerations but also broader geopolitical and diplomatic interests, particularly amid the ongoing dysfunction of the WTO Appellate Body. The novelty of this study lies in integrating substantive WTO legal analysis with institutional and geopolitical considerations in assessing the legality of unilateral trade measures adopted during armed conflict. These findings contribute to the development of international trade law by clarifying the legal limits of emergency trade restrictions and highlighting the challenges faced by the WTO dispute settlement system in responding to contemporary geopolitical crises